Situation Report: Bulgaria, 18 December 1968 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Todor Zhivkov in Moscow New Collective Farm Mergers Criticism of Bulgarian Satirists Continues Miscellaneous Anniversary of Bulgarian Scientific-Technical Unions Celebrated Health Delegation in Moscow Romanian Agricultural Delegation in Bulgaria